Development of Digital Learning Media Based on I Spring Suite 11 to Improve Students' Interest and Learning Outcomes in Economics Subjects at SMA Negeri 11 Malinau in the 2024/2025 Academic Year - Fresdiana Octavia Sarumaha; Sutirman Sutirman (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
This research focuses on the development of digital learning media based on I Spring Suite 11 to assess: 10 t he feasibility of the digital learning media based on I Spring Suite 11; 2) the improvement of student interest in learning Economics at SMA Negeri 11 Malinau; and 3) the improvement of student learning outcomes in Economics at SMA Negeri 11 Malinau.The research method used is research and development (R&D) through the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model with quasi-experimental analysis. The subjects of the research were 10 students from grade X at SMA Negeri 11 Malinau. The instruments used in this study were questionnaires given to media experts, material experts, and teaching practitioners (Economics teachers) to validate the questionnaire instruments and student responses to the digital learning media using the same questionnaires and pretest-posttest learning outcome tests.The research findings are as follows: 1) The feasibility of the I Spring Suite 11-based digital learning media was evaluated by material experts with a score of 78%, categorized as "Feasible"; by media experts with a score of 80%, categorized as "Feasible"; and by teaching practitioners with a score of 85%, categorized as "Highly Feasible." The analysis of the scores showed that the material and media experts' evaluations fell within the "feasible" range (38 ≤ 2)There was a 50.86% increase in student interest in learning, with a pretest average score of 58 and a posttest average score of 91, which meets the product's effectiveness criteria. Based on the pretest-posttest analysis of student interest, the N-gain test resulted in a score of 0.5, which is categorized as "moderate" and falls into the "Good" category. The analysis of the ideal mean score (Mi) showed a value of 50 ≤ X, which means the I Spring Suite 11-based digital learning media is effective for use in the Economics subject. 3)There was a 46.8% improvement in student learning outcomes, with a pretest average score of 54 and a posttest average score of 85 after using the I Spring Suite 11-based digital learning media. Based on the pretest-posttest analysis, the N-gain score was 0.47, which is categorized as "moderate," indicating that the learning media is effective in improving student learning outcomes in Economics.